DNA phenotyping and mapping intragenic deletion mutations in Fanconi anemia: Patterns and diagnostic inferences - Rehab Mosaad; Ghada El-Kamah; Maha Eid; Khalda Amr (Journal of Genetic Engineering and Biotechnology, 2024)
Background: Fanconi anemia is a genetically heterogeneous recessive disorder distinguished by cytogenetic instability, hypersensitivity to DNA crosslinking agents, increased chromosomal breakage, and disturbed DNA repair. To date, Fanconi anemia complementation group (FANC) includes 23 FANC genes identified of which, FANCA gene is the most commonly mutated. The mutation spectrum of the FANCA gene is highly heterogeneous with large intragenic deletions due to Alu elements-mediated recombination.The study aimed to identify different deletion mutations on FANCA gene in Egyptian Fanconi anemia patients by multiplex ligation-dependent probe amplification (MLPA) technique to define the spectrum of FA molecular pathology as a step for disease control. The study included 80 FA patients (36 females and 44 males) whose ages ranged from 4 months to 17 years descending from unrelated consanguineous families referred to the Hereditary Blood Disorders Clinic, National Research Centre (NRC), Egypt. Patients were diagnosed with classical clinical presentation of FA and were confirmed by chromosomal breakage using Diepoxybutane (DEB). Results: The common clinical presentation in our FA patients were the presence of café au lait spots with hyperpigmentation in 65/80 (81%) followed by skeletal defects in 40/80 (50%). MLPA revealed a total of five different intragenic homozygous deletions of FANCA gene in 16 /80 (20%) patients, among them two deletion patterns were novel. Conclusion: Molecular analysis using MLPA could detect pathogenic mutations in 20% of FA patients, our study generated considerable data on causative mutations that was used for genetic counseling and prenatal diagnosis.